Extraction and Separation of Astaxanthin from Marine Products: A Review - Ri Lee, Yu; Tang, Baokun; Ho Row, Kyung (Asian Journal of Chemistry, 2014)
Astaxanthin is a carotenoid used widely in salmonid and crustacean aquaculture to provide the pink color characteristics of that species. The ketocarotenoid astaxanthin can be found in microalgae, yeast and crustacean byproducts. Astaxanthin represents the unique properties of the structure. The astaxanthin molecule has two geometric isomers, cis or trans due to the double bond from the poliene chain. The separation of these isomers is very difficult using ordinary techniques. This paper reviews the current available evidence regarding astaxanthin chemistry and its potential beneficial effects in humans as well as the methods of the extraction and separation of astaxanthin.